Lithuanian Security Police and the Holocaust (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 2003)
The article analyzes the issue of the Lithuanian security police (hereinafter as LSP) taking part in the Holocaust, which has not yet been specifically studied by historiography. The author aims to answer such questions as in what degree and what ways the LSP participated in the persecution of the Jews, and how in this process it co-operated with other divisions of German and Lithuanian police.